2015
DOI: 10.1007/s12325-015-0189-1
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Rivaroxaban Versus Warfarin on Health Care Costs Among Nonvalvular Atrial Fibrillation Patients: Observations from Rivaroxaban Users and Matched Warfarin Users

Abstract: IntroductionNew target-specific oral anticoagulants may have benefits, such as shorter hospital length of stay, compared to warfarin in patients with nonvalvular atrial fibrillation (NVAF). This study aimed to assess, among patients with NVAF, the effect of rivaroxaban versus warfarin on health care costs in a cohort of rivaroxaban users and matched warfarin users.MethodsHealth care claims from the Humana database from 5/2011 to 12/2012 were analyzed. Adult patients newly initiated on rivaroxaban or warfarin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
4
17
0
Order By: Relevance
“…The mean total costs for rivaroxaban was slightly lower compared to warfarin ($17,590 vs. $18,676) where higher pharmacy cost for rivaroxaban was offset by lower hospitalization cost. 10 Similar results were found for cost comparison between dabigatran vs warfarin using HealthCore data. 11 Overall, based on the recently published literature, the NOACs tend to demonstrate better or comparable economic outcomes than warfarin but no data exist to highlight the impact of better adherence to NOACs on cost savings.…”
Section: Introductionsupporting
confidence: 73%
“…The mean total costs for rivaroxaban was slightly lower compared to warfarin ($17,590 vs. $18,676) where higher pharmacy cost for rivaroxaban was offset by lower hospitalization cost. 10 Similar results were found for cost comparison between dabigatran vs warfarin using HealthCore data. 11 Overall, based on the recently published literature, the NOACs tend to demonstrate better or comparable economic outcomes than warfarin but no data exist to highlight the impact of better adherence to NOACs on cost savings.…”
Section: Introductionsupporting
confidence: 73%
“…Lalibert e et al using Premier Perspective Comparative Hospital data demonstrated that rivaroxaban had significantly lower hospitalization cost compared to warfarin ($11,993 vs. $13,255; difference: -$1284; p < .001) per patient during the index hospitalization from 2010 to 2012 29 . Another study by Lalibert e et al also found significantly lower all-cause and AF-related hospitalization costs for rivaroxaban compared to warfarin using Humana data from 2011 to 2012 30 . However, Lalibert e et al did not report costs associated with clinical outcomes: stroke/SE and major bleeding.…”
mentioning
confidence: 91%
“…Not only would large quantities of therapy changes challenge patients and clinicians, but the mass of new NOAC prescription would also have relevant economic influence on the country's obligatory health insurance system covering anticoagulant treatment. It has been shown that NOACs can be cost-effective in specific settings despite higher pharmaceutical costs, because overall costs for anticoagulation related outpatient visits and hospitalizations were reduced compared to warfarin treatment [80][81][82][83][84]. However, just like clinical outcomes, also cost-efficiency estimations have been demonstrated to depend on TTR levels achieved in the VKA group [85,86].…”
Section: Discussionmentioning
confidence: 99%